ANALISIS SISTEM PENGADAAN DAN PEMELIHARAAN BARANG DI KEJAKSAAN NEGERI SURAKARTA - Fransiska Widosari Wibawa (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2019)
ABSTRACTThis research is aimed to know: (1) the implementation of procurement system and item maintenance at the state prosecutor of Surakarta. (2) the obstacles occur in the implementation of procurement system and item maintenance at the state prosecutor of Surakarta. (3) the efforts which done to overcome the obstacles the implementation of procurement system and item maintenance at the state prosecutor of Surakarta. This research is a qualitative fenomenologic research. The technique of collecting the subject of the research is purposive sampling. The source of the data which is used are informants, events or activities; location, documents, and archives. Technique of collecting data used in the research is interview, archives and documentation. The validity of the data checked use triangulation data and triangulation method. Technique of analysing the data use interactive model which is data reduction, data presentation, and conclusion. The result of the research shows that the implementation of procurement system and item maintenance at the state prosecutor of Surakarta runs well. The obstacles occur is procurement of the product of financial capital is hard to get, the procurement is not accepted by the suggested sector, the administration division do not report the factual data of procurement, it lacks the capital goods is very lacking, transparency is not implemented well. The problem solving used are using personal pocket for small maintenance, there is selection toward suggested items, educating about procurement of the capital goods and stationaries, and improving the inventory system. Keywords: System Analysis, Product Procurement, Item Maintenance, the State Prosecutor of Surakarta